Augmentative and alternative communication : engagement and participation - Alant, Erna (Plural Publishing, 2017)
This book examines the basic components of human communication based on the development of meaning between two people and provides a new theoretical framework for integrating the use of Augmentative and Alternative Communication (AAC) strategies into interpersonal interactions. As such, it is an indispensable resource for speech-language pathologists, special education practitioners, and researchers in AAC, as well as for instructors and graduate students in the fields of speech and hearing sciences and special education.